Association of Weather With Day-to-Day Incidence of Myocardial Infarction: A SWEDEHEART Nationwide Observational Study - Mohammad, Moman A. (JAMA Cardiol, 2018)
IMPORTANCE: Whether certain weather conditions modulate the onset of myocardial infarction (MI) is of great interest to clinicians because it could be used to prevent MIs as well as guide allocation of health care resources. OBJECTIVE: To determine if weather is associated with day-to-day incidence of MI. DESIGN, SETTING, AND PARTICIPANTS: In this prospective, population-based and nationwide setting, daily weather data from the Swedish Meteorological and Hydrological Institute were extracted for all MIs reported to the Swedish nationwide coronary care unit registry, Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies (SWEDEHEART), during 1998 to 2013 and then merged with each MI on date of symptom onset and coronary care unit. All patients admitted to any coronary care unit in Sweden owing to MI were included. A total of 280 873 patients were included, of whom 92 044 were diagnosed as having ST-elevation MI. Weather data were available for 274 029 patients (97.6%), which composed the final study population. Data were analyzed between February 2017 and April 2018. EXPOSURES: The nationwide daily mean air temperature, minimum air temperature, maximum air temperature, wind velocity, sunshine duration, atmospheric air pressure, air humidity, snow precipitation, rain precipitation, and change in air temperature. MAIN OUTCOMES AND MEASURES: The nationwide daily counts of MI as outcome. RESULTS: In 274 029 patients, mean (SD) age was 71.7 (12) years. Incidence of MI increased with lower air temperature, lower atmospheric air pressure, higher wind velocity, and shorter sunshine duration. The most pronounced association was observed for air temperature, where a 1-SD increase in air temperature (7.4°C) was associated with a 2.8% reduction in risk of MI (unadjusted incidence ratio, 0.972; 95% CI, 0.967-0.977; P <.001). Results were consistent for non–ST-elevation MI as well as ST-elevation MI and across a large range of subgroups and health care regions. CONCLUSIONS AND RELEVANCE: In this large, nationwide study, low air temperature, low atmospheric air pressure, high wind velocity, and shorter sunshine duration were associated with risk of MI with the most evident association observed for air temperature.